Utilisation of Games and Virtual Reality to Train Competences Relating to Industry 4.0 - Andrzej GRABOWSKI (Zastosowanie gier i rzeczywistości wirtualnej do szkolenia kompetencji związanych z Przemysłem 4.0, 2022)
Implementation of concepts of Industry 4.0 and cyber-physical production systems (CPPS) requires changes to be introduced to production processes and leads to the fact that employees are expected to acquire new competences and skills pertaining to their work tasks in the production industry. It is assumed that employees of factories of the future will have to execute more complicated tasks, such as the monitoring and adjustment of highly automated and complex processes, and supervision and efficient use of machinery, more frequently. Another issue is the utilisation of augmented reality (AR) systems to provide an employee with additional information. This is why the need arises to develop skills covering the management of high volumes of data and machine interaction, as they will be the basic abilities of persons working in the factories of the future. To master new skills and competences, VR training games can be used.
Keywords: Zastosowanie rzeczywistości wirtualnej do szkolenia